Modulation of population density and size of silver nanoparticles embedded in bacterial cellulose via ammonia exposure: visual detection of volatile compounds in a piece of plasmonic nanopaper. Issue 15 (24th March 2016) - Heli, B.; Morales-Narváez, E.; Golmohammadi, H.; Ajji, A.; Merkoçi, A.
Abstract : Corrosive vapour exposure dramatically modulates the population density and size of Ag nanoparticles embedded within nanopaper, leading to a simple nanoplasmonic sensor. Abstract : The localized surface plasmon resonance exhibited by noble metal nanoparticles can be sensitively tuned by varying their size and interparticle distances. We report that corrosive vapour (ammonia) exposure dramatically reduces the population density of silver nanoparticles (AgNPs) embedded within bacterial cellulose, leading to a larger distance between the remaining nanoparticles and a decrease in the UV-Vis absorbance associated with the AgNP plasmonic properties. We also found that the size distribution of AgNPs embedded in bacterial cellulose undergoes a reduction in the presence of volatile compounds released during food spoilage, modulating the studied nanoplasmonic properties. In fact, such a plasmonic nanopaper exhibits a change in colour from amber to light amber upon the explored corrosive vapour exposure and from amber to a grey or taupe colour upon fish or meat spoilage exposure. These phenomena are proposed as a simple visual detection of volatile compounds in a flexible, transparent, permeable and stable single-use nanoplasmonic membrane, which opens the way to innovative approaches and capabilities in gas sensing and smart packaging.